A GUIDING TOOL IN UNANI TIBB FOR MAINTENANCE AND PRESERVATION OF HEALTH: A REVIEW STUDY - Jabin, Farkhunda (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Unani Tibb is a holistic traditional system of medicine. Ever since 1976, WHO has adopted its policy of promoting traditional medicine, Unani Medicine has enjoyed an upsurge of interest, especially in India, where it has been practiced as one of the Indian systems of medicine. Ali et al (2007) opined that “in Tibb, ‘temperament’ is a notion of primary importance, though a difficult theory as it indicates the properties of an atom, a molecule, a cell, a tissue, an organ and human body as a whole”. Temperament of a person represents its physical constitution and tendencies. It is believed in Tibb that imbalance in temperament predisposes human body to various diseases by producing a biotic imbalance with in body. Causes of initial imbalance in temperament lies in more subtle elements of life like air, water, food, rest, activity, work, evacuation of wastes, sleep etc. To quote Bhika (2006a) “health can be preserved and maintained as long as overall quality of humours is in harmony with overall quality of the temperament of the individual and humoural balance is influenced by lifestyle factors.” Hence temperament acts as a guiding force for maintenance and preservation of individuals’ health.